2011
DOI: 10.1016/j.cyto.2010.11.021
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 is expressed in human osteoblasts, but has no direct effect on bone remodeling

Abstract: 1 IL-33 is expressed in human osteoblasts, but has no direct effect on bone remodelingsuggested that expression of IL-33, in contrast to that of IL-1β, is not repressed by PPARγ, likely explaining why IL-33, but not IL-1β, is expressed in adipocytes. The IL-33 receptor ST2L is not constitutively expressed in human bone marrow stromal cells, osteoblasts or CD14-positive monocytes, and IL-33 has no effect on these cells. In addition, although ST2L mRNA is induced by TNF-α and IL-1β in bone marrow stromal cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…This phenomenon may also explain the lack of an inhibitory effect of IL-33 on osteoclast development from human peripheral blood CD14 + cells as observed by us and by others (35,36). This finding is in agreement with an increasing number of studies suggesting the existence of various subsets of human and murine circulating monocytes that differ in their cytokine profile, migratory properties, surface markers, and function.…”
Section: Discussionsupporting
confidence: 80%
“…This phenomenon may also explain the lack of an inhibitory effect of IL-33 on osteoclast development from human peripheral blood CD14 + cells as observed by us and by others (35,36). This finding is in agreement with an increasing number of studies suggesting the existence of various subsets of human and murine circulating monocytes that differ in their cytokine profile, migratory properties, surface markers, and function.…”
Section: Discussionsupporting
confidence: 80%
“…While our findings contribute to the understanding of how IL-33 affects Th2-mediated diseases, it is not clear how IL-33 may function in these Th17-mediated diseases. IL-33 has been shown to cause a wide range of effects, including neutrophil migration, mast cell activation, osteoclast and osteoblast function, wound healing, and others (69)(70)(71). Thus, the ability of IL-33 to affect disease pathogenesis through a multitude of mechanisms has made it an intriguing area of investigation in which a great deal still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 is expressed by bone-forming osteoblasts [10]. Moreover, recent studies reported that IL-33 was expressed in bone tissue, where it plays an important role in bone remodeling by effectively blocking osteoclastogenesis [10,11]; however, the mechanisms underlying the effects of IL-33 on osteoclast formation and function are largely unknown.…”
Section: Introductionmentioning
confidence: 99%